Handbook of plasma processing technology : fundamentals, etching, deposition, and surface interactions - Rossnagel, Stephen M.; Cuomo, J. J.; Westwood, William D. 1937- (Noyes Publications, 1990)
An overview of the technology that describes the advantages provided by plasmas, plasma fundamentals, and a range of plasma processes relevant to the deposition and etching of thin films for microelectronics and other fields.
Keywords: Plasma engineering.; Semiconductors -- Etching.; Plasma etching.; elektronické knihy; electronic books